Tempo czytania ze zrozumieniem w języku polskim na przykładzie uczniów klas ósmych i maturalnych - Moździerz, Tomasz (Neofilolog, 2022)
Reading constitutes for one of the most important activities, both in work and in education. There are three major components to reading: comprehension, decoding and reading speed. The relationship between comprehension and reading speed is a tradeoff; after reaching a certain peak one has to decrease for the other to increase. The knowledge of how fast an average person reads can be a useful tool in planning any activity that requires the use of text, such as a language course. To date Polish linguistics lacks relevant research on the speed of reading with comprehension. The following paper presents part of the doctoral project that aims to answer the questions “How fast and with what level of understanding do Poles read?” The paper sums up two research studies which examined the reading speed and comprehension in Polish of students in the final year of high school and in grade 8 of Polish primary school. Both groups read a non-specific text of medium-difficulty about Sherlock Holmes and completed a 9-item comprehension test. The high school students on average scored 77% on the comprehension test with an average reading speed of 173 words per minute (wpm). On the same text, primary school students scored 66% and read at 156 wpm.